2003
DOI: 10.1177/1466802503003001456
|View full text |Cite
|
Sign up to set email alerts
|

The policy and practice of protective sentencing

Abstract: This article discusses some recent empirical research into the sentencing of dangerous offenders in England and Wales in its wider socio-legal context. It is particularly concerned to draw attention to the ways in which the operation of those procedural constraints that circumscribe judicial discretionary decisions in this area bear little relevance to notions of moral legitimacy, nor the legal rights of offenders, victims or the wider community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…One significant technique of resistance when dealing with protective sentencing measures is the strict application of the principle of proportionality. Although proportionality can be overridden by legislation, the courts have sought to circumscribe the operation of such legislation by limiting its application to exceptional cases only (Freiberg, 2000b;Henham, 2003). When the provisions that allowed longer than proportionate sentences were introduced in Victoria it was not only the legal profession and commentators who thought the principle of proportionality had seen its demise in sentencing in Victoria.…”
Section: Judicial Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…One significant technique of resistance when dealing with protective sentencing measures is the strict application of the principle of proportionality. Although proportionality can be overridden by legislation, the courts have sought to circumscribe the operation of such legislation by limiting its application to exceptional cases only (Freiberg, 2000b;Henham, 2003). When the provisions that allowed longer than proportionate sentences were introduced in Victoria it was not only the legal profession and commentators who thought the principle of proportionality had seen its demise in sentencing in Victoria.…”
Section: Judicial Responsesmentioning
confidence: 99%
“…The experience with longer than proportionate sentences has been the subject of research in recent years. In the United Kingdom, studies have found that courts have been reluctant to utilize the protective sentence powers under s.80(2)(b) of the Powers of Criminal Courts (Sentencing) Act 2000 (UK) (Flood-Page and Mackie, 1998;Henham, 2001Henham, , 2003. There also provisions have been interpreted strictly by the appeal courts, which have used the notion of proportionality to limit any resulting increase in sentence length (Dingwall, 1998;Henham, 2003).…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In this vein, following a recent review of sentencing structures (Home Office, 2001a), Part 12 of the Criminal Justice Act 2003 introduced, inter alia, an indeterminate preventative sentence for violent or sexual offenders for public protection purposes (Padfield, 2003). Offenders would remain in custody under this protective sentence until it is considered that the risk they presented has sufficiently diminished (Henham, 2003).…”
Section: Penal Provisionmentioning
confidence: 99%
“…In addition, it is inevitable that differences between jurisdictions and countries will constrain the generalizability of findings from samples of cases, offenders, courts, or areas. Finally, much of the extant literature examines sentencing decisions generally, or the choice of specific sentencing options (e.g., incarceration), and relatively few have investigated the sentencing of specific types of offenders (e.g., violent offenders) or offences (e.g., common assault; for exceptions in the United Kingdom, see, e.g., Gilchrist and Blissett 2002;Henham 2003;Levi 1989;Speed and Burrows 2006).…”
mentioning
confidence: 99%